Privatisation and liberalisation of the telecommunications industry in Singapore. - Goh, Eric Beng Tiong. (2008)
Our project consists of an analysis of the effects of privatisation of Singapore Telecommunications and the possible future challenges facing the telecommunications industry in Singapore.